Study on the optimal addition of hollow glass microsphere into an anticorrosive cool coating for oil storage tanks. Issue 3 (1st February 2023) - Li, Shihan; Bin, Yuezhen; Wang, Xiaolin; Wu, Xueshan; Zhao, Wei; Liu, Mingrui
Abstract: The addition amount of hollow glass microsphere (HGM) in a newly developed waterborne, fluorocarbon resin-based, anticorrosive cool coating is investigated through a series of indoor tests, combined with real and simulated storage tank tests on site. The heat insulation, corrosion and chemical resistance properties of the coatings with different HGM content are studied. The results show that the temperature reduction of coatings tested indoors rises from 22 to 31.1 °C due to the decrease of thermal conductivity as the HGM content raises from 0% (wt.%) to 16% (wt.%), though the overall reflectivity decreases simultaneously. In addition, both indoor and outdoor spray tests manifest that adding 8 and 12% content of HGM increase the corrosion resistance of the coating. When the content increases to 16%, however, the corrosion resistance becomes worse, which can be attributed to the voids in the coating, along which the corrosive medium enters. Furthermore, all the water, acid and alkaline resistance are improved when the HGM content is 8%. Finally, by optimizing with 8% HGM addition, the temperature reductions of the two simulated tanks in dry-heat desert and tropical marine zones can reach 15 and 18 °C, respectively. And the aging resistance in both two climatic conditions is good.